KINETIKA REAKSI ENZIMATIS EKSTRAK KASAR ENZIM SELULASE BAKTERI SELULOLITIK HASIL ISOLASI DARI BEKATUL - Saropah, Dyah Ayu; Jannah, Akyunul; Maunatin, Anik (ALCHEMY, 2012)
Bran rice is a by-product of rice into rice milling process, the cellulose content of 40-60%, so the potential as a carbon source for the growth of microorganisms such as bacteria to produce enzymes particularly cellulolytic bacteria. The purpose of the study was to determine the diversity of the characters from the cellulolytic bacterial isolates and optimum conditions enzyme (cellulase enzymes rough) so that they can hydrolyze the cellulose to glucose with either rice bran. The characterization includes the determination of pH, temperature and time of optimum crude extract of bacterial cellulolytic enzyme cellulase, determination of Vmax and Km and molecular mass determination of cellulase.Research methods include making media, regeneration of isolates, bacterial growth curve manufacturing, production of cellulase enzymes from bacterial cellulolytic rough at the optimum conditions, the kinetics of enzymatic reaction: substrate concentration factor of the reaction rate (with variation of the concentration of 0.50%, 0.75%, 1 , 00%, 1.25% and 1.50% (w / v)) followed by calculating the Vmax and Km.The results showed that the enzyme cellulase of cellulolytic bacteria isolated from rice bran result that has optimum conditions at pH 7.5, temperature 50 Â° C, 40 min incubation time to produce Vmax 0.0086 units / mL and Km 1.694%.